Analysis Of The Effect Of Blended Learning Models Towards Mathematical Student’s Problem Solving Abilities And Self-Regulated Learning - Meidy Adelina Lumban Toruan; Edy Surya (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2023)
A This study aims to determine: (1) the effect of Blended Learning models towards Mathematical Student’s Problem Solving Abilities and Self-Regulated, (2) the improvement of student’s mathematical problem solving and self regulated learning (3) the advantages of the advantages and disadvantages of blended learning model. This type of research includes descriptive qualitative research using library research methods. The data in this study were obtained from a collection of literature such as theses and journals that are relevant to the topic of discussion, namely Mathematical Student’s Problem Solving Abilities And Self-Regulated. The results show that, 1) Blended Learning Model has a great effect on students' problem solving abilities based on the overall effect size calculation which produces an average effect size of 1.56 where this number is included in the high category and Blended Learning Model has a great effect on student’s self-regulated based on the overall effect size calculation which produces an average effect size of 1.73 2) There is an increase in mathematical the student's problem solving abilities and self-regulated learning that are taught through blended learning models. This can be seen from the achievement of N-Gain value and indicators in the experimental class in the literature which is generally better than the control class. 3) Based on the analysis, it was found that the advantages and disadvantages of blended learning. it can be obtained that the advantages of blended learning models as follows: (a) Learning is more effective and efficient, (b) Improve accessibility. with blended learning, it is easier for learning participants to access material learning. and disadvantages of blended learning is Not evenly distributed facilities owned by students, such as computers and internet access. Even though blended learning requires adequate internet access, if the network is inadequate it will make it difficult for participants to take part in independent learning via online.